Pengembangan peserta didik SD berdasarkan karakteristik perkembangan anak - azzahroh, almas aulia (Maliki Interdisciplinary Journal, 2026)
Elementary school student development must be based on a thorough understanding of the developmental characteristics of children aged six to twelve. This stage is characterized by significant physical, cognitive, emotional, social, moral, and spiritual changes. The purpose of this study was to analyze the developmental characteristics of elementary school students and determine their influence as a basis for effective development and learning approaches. The literature review indicates that elementary school children are in the concrete operational stage, eager to move and play, and enjoy working in groups. Therefore, student development strategies must be responsive, contextual, and prioritize hands-on demonstrations and group collaboration to support optimal growth. Students will grow into academically competent, physically healthy, and strong character integrity individuals in the future if responsive methods, provision of concrete media, and positive behavioral role models work together well.